The Chebyshev Tau Method to Solve Linear Klein Gordon Equation - Mohamad, Siti Zubairah; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2022)
In this study, Chebyshev Tau Method is used to solve the linear system of Linear Klein Gordon equations. To Solve Linear Klein-Gordon Equation using Chebyshev-Tau method. Maple is used to digitally solve the problem. Chebyshev-Tau method prove to be accurate to find Klein Gordon equation. Suggestion future work would be solving the nonlinear Klein Gordon using the same method.